Comparison of the effects of two different local anesthetics used in spinal anesthesia on peripheral and central temperature change: a randomized controlled trial - Azra Ozanbarcı; Hatice Kılınç; Bünyamin Muslu; Safinaz Karabayırlı; Seyfi Kartal; Güler Eraslan Doğanay; Melek Doğancı; Abdullah Kahraman; Oral Mentes; Yasemin Dayıca (BMC Anesthesiology)
Abstract Objective In this study, we aimed to compare the effects of two different local anesthetics with different baricity used in spinal anesthesia on thermoregulation. Materials and methods Our study was conducted on forty full-term pregnant women scheduled for elective cesarean sections under spinal anesthesia. At an operating room temperature of twenty-four degrees Celsius, peripheral body temperature was measured using temperature probes attached to the lower medial parts of the same side’s lower and upper extremities, and central body temperature was measured with a tympanic thermometer. Isobaric levobupivacaine and hyperbaric bupivacaine were used in spinal anesthesia applications. After spinal anesthesia, tympanic temperature, arm and leg temperatures, mean arterial pressure, heart rate, and oxygen saturation were measured and recorded at baseline, the first, third, and fifth minutes, and every five minutes thereafter until the end of surgery. Results In the bupivacaine group, a decrease in tympanic temperature was observed at the third minute and an increase in leg skin temperature at the fifth minute compared to baseline values. In the levobupivacaine group, a decrease in tympanic temperature was observed at the fifth minute, and an increase in leg skin temperature was observed at the third minute. In both groups, within-group comparisons showed a continued decrease in tympanic temperature and increase in leg temperature at all subsequent time points compared to baseline. No statistically significant difference was observed in arm skin temperatures within groups in either group. Conclusion We observed that the effects of hyperbaric bupivacaine and isobaric levobupivacaine used in spinal anesthesia on thermoregulation were similar.